Phylogenetics and Biogeography of Cobra (Squamata: Naja) in Java, Sumatra, and Other Asian Region - Kurniawan, Nia; Putri, Mulyadiane M.; Kadafi, Ahmad M.; Chrestella, Dea J.; Fauzi, Muhammad A.; Kurnianto, Agung S. (Graduate School, Universitas Brawijaya, 2017)
The separation of Sumatra and Java occurred at the end of the Miocene (10 mya) to the end of Pliocene (1.8 mya). The existence of ecological variations and geographic barriers inhibits gene flow through the isolation of adaptation, geography, reproduction, inbreeding, and leading to population segregation. Cobra (genus Naja) distribution became greatly influenced by the geologic condition and sea level. This study was conducted by phylogenetic analysis towards the 16S rRNA gene. Survey was done with Visual Encounter Survey (VES) method on 6 localities. There were 3 locations in Sumatra Island and the others in Java Island. Sample from other Asian region was obtained from Genbank, which are 11 individuals from China, Thailand, and Nepal. DNA extraction was done according to the QIAmpÂ® DNA Mini Kit standard protocol. The forward and reverse 16S sequences are combined with the SequencherTM version 4.1.4 program, then in BLAST (Blast Local Alignment Search Tool) at www.ncbi.nlm.nih.gov.Â Phylogenetic analyzes of clade A (MP = 60, ML = 54, BI = 88) indicate the presence of division into two monophyletic subclade (AI and AII). Subclade AI consists of groups of CobraÂ from Sunda (Thailand, Sumatra and Java). Subclade AII is a group of species N. kaouthia originating from Chumpon Province, Southern Thailand with (MP = 96, ML = 95, BI = 100). Clade B is divided into two subclasses (BI and BII). The result is supported by bootstrap value MP = 93, ML = 99, BI = 100. N. atra of Fujian Province is a sister lineage of the same species from Jiangxi Province (MP = 86, ML = 86, BI = 100).Keywords: Asian, 16s rRNA, Java, Cobra, Sumatra.